Application of a Model of Balance Population in a Ball Mill in the Cement Industry (2014)
This article studies a continuous rotary mill for the cement industry. Specifically, a model is used population balance, where a law constant wear is the constitutive equation, in order to obtain: the distribution mass of the ball in mill, the total consu